Pemanfaatan Abu Tandan Kosong Sawit Sebagai Larutan Elektrolit Pada Aplikasi Sel Elektrokimia - Wahyu Rahmadhan; Yusnimar Sahan; M. Iwan Fermi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Oil palm empty fruit bunches ash is the material which has K+ about 25.68%. K+ has a high value of potential is -2.94 volt (V). That is making K+ be the ion which high possibility for reduction others ion. This research having goals to known DC electricity value (such as voltaic value, current, power , and capacity) within using oil palm empty fruit bunches ash as the electrolyte solution. Part of scrap electronic device that is printed computer board/PCB and Galvanic zinc metal used as electrodes (Kation and Anion). Oil palm empty fruit bunches ash solute made by (b/b) mass ratio, ash: water is 1: 4. And then, the rate of kalium analyzed by flame photometry. As a result, kalium has 60.375 g/L in oil palm empty fruit bunches solutions. After that making an application of electrochemical cell with variates 8, 10 and 12 electrodes cell to calculate voltaic and current values. Beside that other variety is compare ash solution with NaCl solution about DC electricity value with equal of electrode cells (12 cells) and ratio. Results are electrochemical cell having voltaic value, current, power with 12 cells of electrodes is 4.76 V, 0.65 miliampere (mA) and 3.094 miliwatt (mW). The conclusion that oil palm empty fruit bunches ash solution having more high electricity value than NaCl solutions.Keywords: ash, current, NaCl, PCB, volt